Country-Specific Determinants of Agricultural Climate Service Development Pathways in Africa - Hansen, James; Born, Lorna; Solomon, Dawit; Zougmoré, Robert B.; Dinku, Tufa; Mwongera, Caroline; Grossi, Amanda (2021)
The climate services that are available to farmers and other agricultural value chain actors are quite heterogeneous across sub-Saharan African countries. While the literature highlights widespread gaps between available climate services and the needs of farmers and other decision makers, there has been little published analysis of how or why those gaps vary by country. We summarize some of the key differences in agricultural climate services landscape among six countries (Ethiopia, Ghana, Kenya, Mali, Senegal, Zambia), explore factors that may have contributed to those differences, and how country-specific factors enable or constrain efforts to strengthen the contribution of climate services to smallholder agriculture in the near future. These countries are part of an ongoing project, Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA), that aims to enhance the use of climate services and climate-smart technologies for smallholder agriculture. Major differences among countries relate to the maturity and diversity of climate information and delivery channels relative to agricultural needs, public vs. private sector orientation, degree of decentralization, and coordination among the institutions involved. Potential drivers considered are (a) demand, (b) national policies and priorities, (c) capacity to deliver services to rural populations, and (d) the external climate services community. Priority opportunities and major constraints to improving the contribution of climate services to agriculture in the focus countries vary by country in the areas of: (a) addressing climate information gaps, (b) embedding climate services, (c) exploiting digital innovation to deliver services to farmers, (d) building farmers’ capacity to use and influence services, (e) leveraging public and private sector comparative advantage, and (f) creating an enabling policy and funding environment.